Pengaruh Strategi Bauran Pemasaran Terhadap Keputusan Pembelian Produk Teh Tarik Salman - Fitriah, Sherly Annisa; Heryadi, H. D Yadi; Fitriadi, Budhi Wahyu (Jurnal Multidisiplin Dehasen (MUDE), 2025)
A business must have a monthly sales target. If sales have not met the target, efforts must be made to enhance marketing strategies to attract more consumers and thereby increase sales. Salman Tea Tarik Company employs marketing strategies using the marketing mix. The purpose of this research is to determine how the marketing mix influences the purchasing decisions of Salman Tea Tarik products and to identify the most dominant element of the marketing mix affecting the purchasing decisions of Salman Tea Tarik. The research uses a quantitative approach with interview and documentation methods. The sample consists of 99 respondents who are consumers of Salman Tea Tarik, selected using random sampling technique, and the analysis model used is multiple linear regression. The results of this study indicate that the marketing mix, which consists of product, price, place, and promotion, affects the purchasing decisions of Salman Tea Tarik products, and the most influential element of the marketing mix on the purchasing decisions of Salman Tea Tarik products is product, price and promotion.